Product Development Of Illustrated Children's Storybook Entitled "Senja" Into Children's Animated Video Stories - Budi, Hutomo Setia (VCD: Journal of Visual Communication Design, 2019)
Product of illustrated story book for children are very commonly found. In the illustrated story books, there are 2 elements, namely image and text. The image content keeps the child interested with the book as well as helps to tell the event that happened. Existing text describes events and stories. This research discusses the product development of an illustrated story book entitled “Senja” into children's animated video stories. This research uses the research and development methodology. This research was limited to discuss on how to process existing data and images into animation and then merged with narration, background music, and put together to form animated videos. This study also discusses whether additional scenes are needed to improve the storytelling quality in animation. The results obtained from this study that the existing image assets in the illustrated children's storybook can be processed and developed into decent children's animated video stories by adding scenes to support storytelling. Background music that suitable with the scene was also needed to build the atmosphere in the animated video. Narration was also needed to strengthen the scene and storytelling.